Applying Double Diamond Methodology to Improve Bumikan Website's User Experience in the Funeral Industry - Miizan Nur Qisthi; Ferdiansyah; Nasya Fatika Augusta; Nur Azizyah Puteri Dewita; Syti Sarah; Rangga Gumelar (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The occurrence of funerals is infrequent, but when the need arises, individuals must be prepared to manage the associated processes. Despite living in an information-rich era, many individuals, particularly the youth, face significant challenges in executing funeral arrangements due to a lack of knowledge and access to relevant resources. The Bumikan platform was developed to address this gap by facilitating the funeral process. To enhance the user experience for prospective users, the platform was designed through a multi-faceted approach that integrates design thinking, lean startup principles, agile development, and the double diamond framework. Usability testing was employed to evaluate customer satisfaction and the ease of use of the platform. The test results affirm the design's effectiveness, ensuring a smooth user experience. In conclusion, by synthesizing various frameworks and prioritizing user-centric design, the Bumikan platform exemplifies a comprehensive development approach, aiming to provide a valuable and impactful tool for individuals navigating the complexities of bereavement.